solve for x in one of the equations. Then whatever value you get for x(x will equal an equation in terms of y) plug it into the second equation. That equation will now contain only y's. Solve for y. Now plug that y value into the first equation. Solve for x.
you should note that you dont have to neccisarily solve for x first. you can do this by solving one of those equations for y first, if you choose to.
4x+5y=-6
x=(-6-5y)/4
plug into second equation
(-6-5y)/4-(5/3)y=-2
lcd = 12
(-18-15y)/12-(20y)/12=-2
(-1/12)(18+15y+20y)=-2
18+35y=24
y=6/35
plug into other equation and you'll get an x value
4x+5(6/35)=-6
4x=(-30/35)-(210/35)
divide by 4 to isolate x
x= -240/140
simplify
x=-12/7
2007-07-15 11:11:40
·
answer #1
·
answered by Anonymous
·
0⤊
1⤋
Substitution is just solving one equation for a variable and plugging that result into the other equation. To work out your substitution problem, follow the steps below:
1.) The second equation seems easier to solve for one variable, so I will solve for x in that equation. (Note: It doesn't matter which variable you solve for, nor does it matter which equation you decide to solve for)
x - 5/3y = -2
x = 5/3y - 2
That simple for step 1.
2.) The next step is the actual "substitution". Here you substitute your solution to x from the first equation into the x in the other equation.
4x + 5y = -6
4(5/3y - 2) + 5y = -6
3.) Now you solve for y in this equation until you get a solution for y.
4(5/3y - 2) + 5y = -6
20/3y - 8 + 5y = -6
35/3y - 8 = -6
35/3y = 2
y = 6/35
There is your solution to y in the problem.
4.) Now you take your solution to y and plug it into any of the original equations you want and solve to find a numerical value for x.
4x + 5y = -6
4x + 5(6/35) = -6
4x + 30/35 = -6
4x = -240/35
x = -240/140 or x = -12/7
There you go. You have found the values for the ordered pair (x,y) as (-12/7, 6/35). Hope this helps :)
2007-07-15 18:23:53
·
answer #2
·
answered by ? 2
·
0⤊
0⤋
x = - 2 + (5/3) y
4x + 5y = - 6
- 8 + (20/3) y + 5y = - 6
(20 / 3) y + 5y = 2
20 y + 15 y = 6
35 y = 6
y = 6 / 35
x = - 2 + (5 / 3) (6 / 35)
x = - 2 + 2 / 7
x = - 12 / 7
Solution
x = - 12 / 7 , y = 6 / 35
2007-07-16 13:24:12
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
yeah that's the correct answer.
the way i did is that I solved x in "x-5/3y= - 2, " then substitued this x into the first equation, and found y=6/35.
Finaly, sub 6/35 into second eq. to solve for x.
This problem involves some fractions, so maybe you need to becareful with the fractions.
2007-07-15 18:19:05
·
answer #4
·
answered by mike 1
·
0⤊
0⤋
i could never stand substitution for some reason i would even go more out of the way for some problems just to use elimination
2007-07-15 18:13:02
·
answer #5
·
answered by doctaphil89 2
·
0⤊
2⤋
isolate 1 variable
4x+5y=-6
5y=-6-4x
y=-1.2-0.8x
plug into other
x-5/3y=-2
x-5/3(-1.2-0.8x)=-2
x+2+1.33x=-2
2.33x=-4
x=-1.7
plug into other
-6.8+5y=-6
5y=.8
y=0.16
x=-1.7
y=0.16
same as you answer just as a decimal
2007-07-15 18:07:14
·
answer #6
·
answered by Dill 4
·
0⤊
3⤋
x= 43/6
so you can figure out y
2007-07-15 18:16:18
·
answer #7
·
answered by Krishna K 2
·
0⤊
1⤋